2011
DOI: 10.1021/jp202654v
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Energy Migration in Solid versus Liquid Host Matrices for Concentrated Perylenediimide Dye Solutions

Abstract: In this paper, we continue our evaluation of Forster-type theories of exciton diffusion in disordered environments. The perylenediimide dye Lumogen Red is used as a donor molecule in two different liquids, CHCl(3) and dimethylformamide, and the energy transfer to the acceptor molecule Rhodamine 700 is measured using time-resolved fluorescence decays. The exciton motion is measured over Lumogen Red concentrations ranging from 1 × 10(-4) to 5 × 10(-2) M, and the results are compared to previous results for excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…a factor of 2 to 4 larger than the diffusion constant determined from the above EEA monitoring experiments. Extensive investigations of rigid solutions of perylene red in PMMA films 57,72,85,[92][93][94] concluded that inhomogeneous spectral broadening explains a similar discrepancy between the measured diffusion coefficients and the values expected from eqn (12): after the first few exciton hopping events and simultaneous energy relaxation, the blue-most absorbing dyes would no longer contribute to electronic excitation transfer, thus reducing the concentration of dyes effectively available for excitation energy transport. Comparatively, the diffusion coefficient D measured in the present (R18/F5-TPB) loaded ONPs is one order of magnitude larger than in perylene red PMMA films with same dye loadings, 57 and the saturation of the D value in ONP100 occurs at significantly larger dye concentration.…”
Section: Discussionmentioning
confidence: 70%
“…a factor of 2 to 4 larger than the diffusion constant determined from the above EEA monitoring experiments. Extensive investigations of rigid solutions of perylene red in PMMA films 57,72,85,[92][93][94] concluded that inhomogeneous spectral broadening explains a similar discrepancy between the measured diffusion coefficients and the values expected from eqn (12): after the first few exciton hopping events and simultaneous energy relaxation, the blue-most absorbing dyes would no longer contribute to electronic excitation transfer, thus reducing the concentration of dyes effectively available for excitation energy transport. Comparatively, the diffusion coefficient D measured in the present (R18/F5-TPB) loaded ONPs is one order of magnitude larger than in perylene red PMMA films with same dye loadings, 57 and the saturation of the D value in ONP100 occurs at significantly larger dye concentration.…”
Section: Discussionmentioning
confidence: 70%
“…12 Experiments on molten anthracene and naphthalene showed that these liquids could support long triplet lifetimes and enhanced triplet diffusion lengths. [13][14][15] Later theoretical 16 and experimental [17][18] work on energy migration in dye molecule solutions demonstrated that liquid environments could also enhance singlet exciton diffusion rates. Presumably, the ability of liquid-state molecules to sample multiple configurations during their excited state lifetimes prevents the formation of static low energy trap sites.…”
Section: Introductionmentioning
confidence: 99%
“…For quite some time, perylenediimides (PDIs) have attracted substantial scientific interest thanks to their unique set of chemical, photochemical, and photophysical properties. In particular, PDIs coupled to other chromophoric species have been considered excellent model systems for gleaning insights into various fundamental and applied aspects of a diverse spectrum of photonic and electronic materials. Since PDI functionalization chemistry typically occurs either at the imide site(s) or in the bay region (1-, 6-, 7-, or 12-positions), it allows one to engineer linear or ladder-type multichromophoric PDI-based oligomers with a desired envelope of functional properties. , However, we note that efficient construction of multimeric isomerically pure ladder-type structures is often limited by nontrivial separations of mixtures of 1,6- and 1,7-disubstituted PDIs, although a few successful examples have been reported. PDI-based molecular systems are also expected to display solvent programmable propensity toward aggregation, making them ideal candidates for the study of energy and electron transfer processes in both aggregated and nonaggregated forms. ,, Here, we aimed at utilizing highly emissive PDI chromophores as building blocks to construct electronically coupled ladder-type molecular systems that would manifest relatively strong electronic intramolecular interactions and desirable photophysics as a result of being connected through sp-hybridized acetylene bridges. In this case, the extent of electronic coupling can be tuned by varying the number of acetylene bridging units between adjacent PDI chromophoric species.…”
Section: Introductionmentioning
confidence: 99%